An ICU Expansion of a Novel Chaplain Intervention, "This is My Story," to Support Interdisciplinary Medical Teams Delivering Care to Non-Communicative Patients in an Academic Medical Center - Wilson, Jason (Journal of religion and health, 2023)
The intervention "This is My Story" (TIMS) was previously developed and presented as a case study involving chaplains and support to non-communicative patients (Tracey et al in J Religion Health, 60(5):3282-3290, 2021). This further investigation aims to determine feasibility by looking at eight criteria: acceptability, demand, implementation, practicality, adaptation, integration, expansion, and limited-efficacy testing (Bowen et al in Am J Prev Med 36(5):452-457, 2009). Chaplains conducted recorded conversation with a patient’s loved one, then it was edited for brevity and succinctness, and uploaded to the patient’s medical chart and can be listened to at any time by medical providers. A completed interview, posted to the patient’s electronic medical record (EMR), and able to be listened to by the medical team, was found to be contingent upon two factors: proximity to time between referral to call completion and amount of clinical experience of the chaplain.